Unilateral Bifurcated Renal Pelvis with Partial Duplication of Ureter and An Accessory Renal Artery: A Case Report - KC, Sudikshya; Rauniyar, Shyam Babu (Med Phoenix, 2018)
Duplication of renal collecting system is the most common upper urinary tract congenital anomaly. Duplex collecting system is presence of complete or partial double pelvicalyceal system which is associated with single or double ureter. A duplicated ureter is commonly found in association with other congenital anomalies which are often an incidental finding during radiograph of abdomen and pelvic region for other purposes. During routine dissection of a female cadaver of about 60-65 years old, in the Department of Anatomy, National Medical College, Birgunj; the bifurcated renal pelvis with incomplete duplication of ureter and an accessory renal artery was found on left side. Two segments of ureter coalesce 2.4 cm distal to the lower pole of kidney and form a single ureter. Right sided renal pelvis and ureter was normal. Both the ureters opened in the urinary bladder with single opening as usual. Knowledge of normal anatomy as well as developmental anomalies of the urinary system is of utmost importance not only for anatomists, radiologists and urologists but also to surgeons for uneventful renal transplant. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 91-94